Clinical Response Description of Primary Brain Tumor Patients with Radiotherapy at The Radiation Oncology Department, Dr. Hasan Sadikin General Hospital, Bandung - Lestari, Windha; Utama, Marhendra Satria; Baraqbah, Hasan (Indonesian Journal of Cancer, 2025)
Background: Brain tumors, marked by abnormal cell divisions, are classified as primary or secondary based on their origin. Effective management involves a comprehensive strategy, with radiotherapy employed as definitive, adjuvant, or palliative treatment. This study aimed to examine the clinical responses of primary brain tumor patients receiving radiotherapy at RSUP Dr. Hasan Sadikin, Bandung, from 2020 to 2022.Method: This descriptive research utilized total sampling, including 19 medical records of primary brain tumor patients who underwent radiotherapy at Hasan Sadikin Bandung Central General Hospital between 2020 and 2022.Results: Primary brain tumor patients undergoing radiotherapy were primarily aged 0-18 years (47.4%), predominantly female (63.2%), and from the West Priangan region (36.8%), with headaches as the chief complaint (47.4%). Tumor grading was evenly distributed among grades 1, 3, and 4 (26.7% each), with the main anatomical locations in the temporal lobe and cerebellum (33.3% each). Histopathologically, astrocytoma and medulloblastoma were most common (21% each), and the majority received adjuvant radiation therapy (57.9%), primarily via Intensity Modulated Radiation Therapy (IMRT) (68.4%). All patients received doses ≤ 2 Gy per fraction (100%), with most receiving 20 fractions (94.7%). The mean time to start radiotherapy was 44.37 ± 22.25 days, and the mean duration was 88.11 ± 21.32 days post-diagnosis. Tumor size decreased from 4.33±1.66 cm before treatment to 1.28±1.74 cm afterward, with 50% of patients achieving a complete clinical response.Conclusion: Children and adolescents (0-18 years) from West Priangan, primarily females, made up the majority of primary brain tumor patients receiving radiotherapy. Headache was the most common symptom, with tumors mostly in the temporal lobe and cerebellum. Astrocytoma and medulloblastoma were the dominant histopathological types. Patients primarily underwent IMRT, with doses ≤ 2 Gy per fraction, often over more than 20 fractions. Radiotherapy lasted between 44 and 88 days, significantly reducing tumor size, and most patients had a complete response.